2020
DOI: 10.3390/agriculture10020032
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas fluorescens MZ05 Enhances Resistance against Setosphaeria turcica by Mediating Benzoxazinoid Metabolism in the Maize Inbred Line Anke35

Abstract: Beneficial rhizobacteria can inhibit foliar pathogen infection by activation of defense responses, yet it the mechanisms of rhizobacteria-induced disease resistance remain largely unknown. Here, inoculation of susceptible maize plants with Pseudomonas fluorescens MZ05 significantly reduced disease occurrence caused by the leaf pathogen Setosphaeria turcica. Gene expression profiles of MZ05-inoculated plants were investigated by RNA-sequencing analyses, showing that several differentially expressed genes were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…High accumulation of DIMBOA greatly elevates the ability of plants to withstand the invasion of diverse pathogens [25]. It is increasingly recognized that beneficial soil microorganisms such as Pseudomonas fluorescens and arbuscular mycorrhizal fungus (AMF) can induce the biosynthesis of DIMBOA in leaves, which contributes to increased resistance of maize plants against pathogens including Rhizoctonia solani and Setosphaeria turcica [26,27]. Mounting evidence has indicated that biofilm formation is essential for root colonization by beneficial soil bacteria [12,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High accumulation of DIMBOA greatly elevates the ability of plants to withstand the invasion of diverse pathogens [25]. It is increasingly recognized that beneficial soil microorganisms such as Pseudomonas fluorescens and arbuscular mycorrhizal fungus (AMF) can induce the biosynthesis of DIMBOA in leaves, which contributes to increased resistance of maize plants against pathogens including Rhizoctonia solani and Setosphaeria turcica [26,27]. Mounting evidence has indicated that biofilm formation is essential for root colonization by beneficial soil bacteria [12,28].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria-forming biofilms containing exopolysaccharides hold bacterial communities together, which help them colonize the host rhizosphere [12]. Many studies have demonstrated that there is a threshold level for root colonizing bacteria to trigger ISR of host plants against microbial pathogens [4,5,11,26]. In nature, different bacteria species are able to interact synergistically in the formation of biofilms and enhance the ability of plants to inhibit pathogen infection [12].…”
Section: Introductionmentioning
confidence: 99%
“…DIMBOA‐treated plants recruit specific bacterial families and species such as Pseudomonas putida , thereby increasing plant resistance to several stresses (Neal & Ton, 2013). P. fluorescens increases DIMBOA and primed resistance against the fungal pathogen Setosphaeria turcica in maize (Zhou, Ma, Lu, Zhu, & Yan, 2020). The populations of bacterial plant pathogens such as Xanthomonadaceae and Agrobacterium tumefaciens decreased in benzoxazinoid‐treated plants (Cotton et al, 2019; Kudjordjie et al, 2019).…”
Section: Wireless Communication: Signal Input‐transfer‐output Modelmentioning
confidence: 99%
“…DIMBOA-treated plants recruit specific bacterial families and species such asPseudomonas putida , thereby increasing plant resistance to several stresses (Neal & Ton, 2013). P. fluorescens increases DIMBOA and primed resistance against the fungal pathogenSetosphaeria turcica in maize (Zhou, Ma, Lu, Zhu & Yan, 2020). The populations of bacterial plant pathogens such as Xanthomonadaceae and Agrobacterium tumefaciens decreased in benzoxazinoid-treated plants (Cotton et al , 2019, Kudjordjie et al , 2019.…”
Section: ? Wireless Signal Transfermentioning
confidence: 99%